THE COMPARATIVE CHARACTERISTICS OF THE FOURTH AND THE FIFTH WAVES OF THE NEW CORONAVIRUS INFECTION IN CHILDREN - Елкина, Татьяна Николаевна; Грибанова, Ольга Александровна; Пирожкова, Наталья Игоревна; Лиханова, Маргарита Геннадьевна; Кузнецова, Анастасия Сергеевна (Mother and Baby in Kuzbass, 2023)
The aim of the research – the comparative characteristics of the course of the new coronavirus infection (COVID-19) in children in different periods of the pandemic. Materials and methods. The comparative retrospective analysis of outpatient records of children in Novosibirsk was carried out. The first group includes patients who had the new coronavirus infection in October-December 2021 (the fourth wave of the pandemic). The second group consisted of patients with a registered infection in January-March 2022 (the fifth wave of incidence). The nature and severity of clinical symptoms of COVID-19, the presence of bacterial complications, the amount of drug therapy at the outpatient stage as well as the need to prescribe antibacterial agents were analyzed. Statistical processing of the material was carried out using the SPSS software package (version 26.0). Results. The clinical picture of the fourth wave of COVID-19 was characterized by nasal congestion, mucous nature of the nasal secretion, dry cough, pharyngoscopic signs of tonsillitis, auscultatory symptoms of bronchitis, development of the bacterial complications (acute otitis media, acute rhinosinusitis), longer disease duration, need for more medications, including systemic antibiotics. For the fifth wave of COVID-19, hoarseness, serous nasal discharge, symptoms of pharyngitis, faster recovery, use of fewer symptomatic therapies were typical. Conclusion. It has been reliably proven that COVID-19 in different periods of increased morbidity has specific clinical course, which must be taken into account when determining the tactics of managing patients in the pediatric area.